The impact of risk, crisis and disaster management strategies on organizational effectiveness. A pilot study in the United Arab Emirates - Mohamed, Shahrulanuar; Abdulla Alhosani, Abdulla Abdulaziz; Kudus, Norliah; Ab Rahman, Zaizul (Auricle Global Society of Education and Research, 2024)
The pragmatic study assessed the impact of risk, crisis and disaster management strategies on organizational effectiveness in the UAE. The investigation study utilized a survey research design with quantitative approach. A sample size of 100 participants was carefully chosen using a table developed by Morgan & Krejcie (1970). Information was gathered by means of structured questionnaires. Data was evaluated using descriptive statistics such as tables, frequencies, percentages and means. The researcher also used inferential statistics such as partial Least Squares, Structural equation modelling and multiple regression analysis to determine the relationship between the study variables. The researcher used stratified random sampling to garner data for the research study. The study findings indicated that disasters preparedness strategy has significant effect on the organisational effectiveness in UAE aviation industry.The project concluded that Disaster preparedness and prevention strategies for crises like the COVID-19 pandemic are important in gradients that any organisation should give priority in its development process.Organisations that have survived throughout the ages are those that respect the principle of rationalisation in its decision making.From the schoolwork findings, the academic recommended that the Aviation Industry in the UAE should prioritize the development and implementation of effective disaster preparedness policies, provide adequate support and resources to individual government organs in order to have sanity and normalcy in the development process of the nation.